Academic procrastination and internet addiction in university students of Lima Metropolitana - Castro Bolaños, Silvia (2017)
The purpose of this investigation is determining the relationship between academic procrastination and internet addiction in young students of a private university in Lima Metropolitana. In the sample were considered 168 students of both genders, aged between 18 and 25 years of a private university in Lima Metropolitana. The materials used were a procrastination scale and an internet addiction scale. The results show a positive and significant relationship between academic procrastination and internet addiction.